Gerador de indução com excitação estática, filtro ativo e armazenamento de energia para sistemas eólicos isolados - Trapp, Jordan Gustavo (2013)
The growing global demand for electricity, increasing scarcity of the conventional energy sources and the need to reduce environmental impacts contributed to the pronounced development of new technologies based on clean and renewable energy sources. In this context, the wind power is the technology that has had a greater development in recent decades. This source has played an important role in the advancement of alternative sources in the world energy matrix, because the technology is already consolidated and is economically viable. Accompanying the technological development of the alternative sources, the induction generator has stood out among the generators with the technology best suited to generating electricity for isolated energy systems. With this motivation, this thesis proposes a new configuration for an isolated wind energy conversion system using variable speed turbines, in which the induction generator is electronically excited by means of a static compensator. Also, the generator is associated to a shunt active filter for compensation of non-linear and unbalanced loads, and with a battery bank for energy storage and DC bus stabilization. It is also discussed the main problems with the induction generator related to the magnetization characteristic and its dynamic model, and the proposed solutions to mitigate these problems. The results confirm the effectiveness of the proposed wind energy conversion system, showing its operational capability with variable load and variable turbine speed. Finally it is presented the main conclusions of this work and suggestions for future works in the same line of research.